Low voltage ZnO thin-film transistors with Ti-substituted BZN gate insulator for flexible electronics - Cho, Kwang-Hwan; Kang, Min-Gyu; Oh, Seung-Min; Kang, Chong-Yun; Lee, YoungPak; Yoon, Seok-Jin (ELSEVIER SCIENCE SA, 2010)
We report the fabrication of ZnO based thin-film transistors (TFTs) with high-k gate insulator of Ti-substituted Bi1.5ZnNb1.5O7 (BZN) films. (Bi1.5Zn0.5)(Zn0.4NB1.43Ti0.3O7) film deposited on Pt/Ti/SiO2/Si substrate by pulsed laser deposition at room temperature exhibits high dielectric constant of 73 at 100 kHz, while BZN film shows much lower dielectric constant of 50, respectively. The increasing dielectric constant with increasing Ti substitution can be attributed to the presence of a highly polarizable TiO6 octahedra and its strong correlation with the NbO6 octahedra. All room temperature processed ZnO based TFTs using Ti-substituted BZN gate insulator exhibited filed effect mobility of 0.75 cm(2)/Vs and low voltage device performance less than 2.5 V. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: DIELECTRIC-PROPERTIES; ORGANIC TRANSISTORS; PYROCHLORE; GLASS